Humanizing Technology: Pustakawan di Tengah Arus Automasi - Febtrisia Aslami; Gustina Erlianti; Marlini (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The development of automation technology and artificial intelligence has brought significant changes to library service systems, particularly in improving the efficiency and speed of information access. However, the dominance of technology has also raised concerns about the decreasing human dimension in librarians’ services. This article examines how librarians can maintain their human-centered roles amidst the implementation of library automation through an analysis of national and international literature published over the past five years. The findings show that automation and artificial intelligence do not replace the role of librarians; instead, they transform it into more strategic functions such as information literacy facilitation, user assistance, and the preservation of ethical values in library services. The concept of humanizing technology is therefore essential to ensure that technology remains integrated with human values so that library services are not only efficient but also user-oriented.